A Noninvasive Computational Method for Fluid Resuscitation Monitoring in Pediatric Burns. Issue 1 (January 2015) - Stewart, Camille L.; Mulligan, Jane; Grudic, Greg Z.; Pyle, Laura; Moulton, Steven L.
<x xml:space="preserve">Abstract</x> The fluid resuscitation needs of children with small area burns are difficult to predict. The authors hypothesized that a novel computational algorithm called the compensatory reserve index (CRI), calculated from the photoplethysmogram waveform, would correlate with percent total body surface area (%TBSA) and fluid administration in children presenting with ⩽20% TBSA burns. The authors recorded photoplethysmogram waveforms from burn-injured children that were later processed by the CRI algorithm. A CRI of 1 represents supine normovolemia; a CRI of 0 represents the point at which a subject is predicted to experience hemodynamic decompensation. CRI values from the first 10 minutes of monitoring were compared to clinical data. Waveform data were available for 27 children with small to moderate sized burns (4–20 %TBSA). The average age was 6.3 ± 1.1 years, the average %TBSA was 10.4 ± 0.8%, and the average CRI was 0.36 ± 0.03. CRI inversely correlated with the %TBSA (P < .001). Twenty children were transferred with an average reported %TBSA of 16.5 ± 1.4%, which was significantly higher than the actual %TBSA (P < .001). CRI correlated better with actual %TBSA compared to reported %TBSA (P = .02). CRI correlated with the amount of fluid resuscitation given at the time of CRI measurement (P = .02) and was inversely related to total fluids given per 24 hours for children with adequate urine output (>0.5 ml/kg/hr) (P < .001). The CRI is decreased in children with small to moderate size burns, and correlates with %TBSA and fluid administration. This suggests that the CRI may be useful for fluid resuscitation guidance, warranting further study.